The effect of different hydrogen terminations on the structural and electronic properties in the triangular array graphene nanomeshes. Issue 15 (30th January 2017) - Tang, G. P.; Zhang, Z. H.; Deng, X. Q.; Fan, Z. Q.; Zhang, H. L.; Sun, L.
Abstract : Constructing periodic nanoscale holes on graphene to form graphene nanomeshes (GNMs) is an effective way for opening band gaps. The GNMs terminated by di-hydrogenation could open a sizable band gap due to the stronger on-site potential between holes. Abstract : Constructing periodic nanoscale holes on graphene to form graphene nanomeshes (GNMs) is an effective way for opening band gaps. The effect of different hydrogen terminations on the structural and electronic properties in the triangular array graphene nanomeshes is investigated systematically from first-principles. The calculated results from the formation energy, Gibbs free energy, and phonon band structure reveal that the di-hydrogenated sp 3 hybridization is the most favorable structure for the hole edges of GNMs except that the other hydrogen terminations may be stable under extremely-poor hydrogen conditions. The electronic properties of GNMs are very sensitive to edge hydrogen terminations, the GNM could be a semimetal, semiconductor, magnetic half-semimetal, or Bipolar Magnetic Semiconductor (BMS) by varying the edge hydrogen terminations, and the GNMs terminated by di-hydrogenation could open a sizable band gap due to the stronger on-site potential between holes, while the gap width could be tuned between semimetallic and semiconducting states by varying the neck width.